External training loads and smartphone-derived heart rate variability indicate readiness to train in elite soccer - Chrismas, B. C. R.; Taylor, L.; Thornton, H. R.; Murray, A.; Stark, G. (International Journal of Performance Analysis in Sport, 2019)
Player readiness can affect the ability to perform and tolerate prescribed training load (TL); therefore, in a time-efficient and practice compatible manner, practitioners need objective evidence to inform readiness to train. Six male professional footballers (mean ± standard deviation [SD]; 26 ± 2 years, 79.0 ± 4.9 kg, 1.82 ± 0.05 m) participated. Heart rate variability (HRV) was recorded using a smartphone application prior to the daily training sessions (247 training sessions [41.17 ± 7.41 per player]). External TL was monitored during training using global positioning system devices. Linear mixed models were used to examine variations in HRV and TL across the study period and to determine relationships between HRV and TL. Differences in TL and HRV were expressed as standardised effect sizes (ES) ± 90% confidence limits. Changes in HRV (outcome) were expressed as the expected change for a 2-SD change in TL (predictor). Across the study period, all external TL measures varied substantially, demonstrating weekly fluctuations in load (ES range = 0.00-7.40). The relationship between morning HRV and external TL ranged from -0.10 for distance and 1.89 for equivalent distance index (EDI). Overall, EDI demonstrated the strongest relationship with morning HRV; therefore, EDI and smartphone-derived HRV may provide an indicator of readiness to train within elite soccer.